The Relationship Between Taking Maths Literacy at School and a Student's Ability to do Accounting at Tertiary Level - Carvalho, Carmen (The IIE, 2020)
Does the Mathematics Literacy content taught at school adequately prepare students to achieve success in accounting at tertiary level? More specifically, did taking Maths Literacy at school make students doubt their ability to successfully complete accounting at tertiary level? Democracy in South Africa brought about changes to the education system to make it more equitable and accessible to all South Africans. One of these changes was the introduction of Maths Lit in 2006 into high schools as a means to improve students’ maths literacy. A review of the literature revealed that not much research has been undertaken to find a correlation between taking Maths Lit and achieving low marks in accounting, there is more literature on the effects of Maths Lit on the science subjects. This research is multifaceted in that it focuses on establishing possible links between low accounting marks at first year tertiary level and having taken Maths Lit as a school subject. It further investigates whether low self-efficacy or confidence levels are caused by taking Maths Lit at school which then impacts negatively on the ability to do accounting at tertiary level. For the ten participants in this study it was derived that having taken Maths Lit at school increased a student’s confidence as students stated they no longer ‘felt stupid’. This had a spill-over effect resulting in improved marks for most of the subjects taken at school. This result, however, needs to be further researched to establish if the increased confidence levels equate to higher marks and a deeper understanding of and an ability to do accounting at a tertiary level.
Keywords: Mathematics Literacy; Accounting at Tertiary Level; Low self-efficacy; Improved marks